2017
DOI: 10.1111/tbj.12854
|View full text |Cite
|
Sign up to set email alerts
|

Bracketed radioactive seed localization vs bracketed wire-localization in breast surgery

Abstract: Multiple localizers placed in a bracketed fashion facilitates excision of radiographically extensive breast lesions. In this study, bracketed radioactive seed localization (bRSL) was compared to bracketed wire localization (bWL). We hypothesized that bRSL would achieve adequate margins and decrease re-operation rates with similar or less specimen volumes (SV) than bWL. Retrospective review identified patients who underwent bracketed breast procedures at an academic medical center. Data collected included patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 20 publications
0
9
0
Order By: Relevance
“…Bracketing is possible with radioactive seeds, and has been shown to be superior with seeds than wire. A retrospective study showed a decrease in re excision rate with similar specimen volumes and lower rate of mastectomy for bracketed seed localization when compared with wire localization (38).…”
Section: Updatementioning
confidence: 99%
“…Bracketing is possible with radioactive seeds, and has been shown to be superior with seeds than wire. A retrospective study showed a decrease in re excision rate with similar specimen volumes and lower rate of mastectomy for bracketed seed localization when compared with wire localization (38).…”
Section: Updatementioning
confidence: 99%
“…9 Our study demonstrated negative margins in 68 per cent of cases for bRSL. In a study by Da Silva et al 6 published in 2018, patients were significantly more likely to undergo a mastectomy in the bWL group than in the bRSL group (24% vs 7%; P < 0.01). Our study supports that conclusion with only one patient converted to mastectomy (4%).…”
Section: Discussionmentioning
confidence: 93%
“…Lesions requiring bracketed localization include radiologically evident, nonpalpable lesions or lesions that extend beyond the palpable area on imaging. In a study by Da Silva et al, 6 patients with bWL are 3.9 times more likely to undergo reoperation than patients with bRSL, including increased rate of conversion to mastectomy.…”
mentioning
confidence: 97%
“…WGL has been the historical gold standard for non-palpable tumour localization. WGL is effective regarding lesion localization, but reoperation rates range from 2.8 to 53 per cent, as a result of tumour-positive resection margins 33 , 34 . Also, WGL is associated with logistical challenges, wire dislocation, kinking or fracturing, and patient discomfort 3 .…”
Section: Discussionmentioning
confidence: 99%